2021
DOI: 10.3390/ijms22147309
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profile of Cytokines, Regulatory Mediators and TLR in Mesenchymal Stromal Cells after Inflammatory Signaling and Cell-Passaging

Abstract: Adult human subcutaneous adipose tissue (AT) harbors a rich population of mesenchymal stromal cells (MSCs) that are of interest for tissue repair. For this purpose, it is of utmost importance to determine the response of AT-MSCs to proliferative and inflammatory signals within the damaged tissue. We have characterized the transcriptional profile of cytokines, regulatory mediators and Toll-like receptors (TLR) relevant to the response of MSCs. AT-MSCs constitutively present a distinct profile for each gene and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…However, routine phenotypic characterizations alone cannot be used to identify differences in the functional properties of these cells, which has been reflected in the lack of consistent and reproducible success in many MSC-related clinical trials. Recently, several groups have attempted to compare molecular and functional similarities among multiple sources of MSCs using independent omics-based methods; i.e., transcriptional profiling ( Elahi et al., 2016 ; Merimi et al., 2021 ; Sargent et al., 2018 ), proteomics ( Billing et al., 2016 ; Kehl et al., 2019 ), and secretome analysis ( Mizukami et al., 2019 ; Petrenko et al., 2020 ; Shin et al., 2021 ; Wangler et al., 2021 ). However, while data gleaned from these studies somewhat complement conclusions drawn from phenotypic analysis, one major drawback is that each of these studies focus on a different profiling methodology, which makes it difficult to establish a molecular equivalency among the various datasets.…”
Section: Introductionmentioning
confidence: 99%
“…However, routine phenotypic characterizations alone cannot be used to identify differences in the functional properties of these cells, which has been reflected in the lack of consistent and reproducible success in many MSC-related clinical trials. Recently, several groups have attempted to compare molecular and functional similarities among multiple sources of MSCs using independent omics-based methods; i.e., transcriptional profiling ( Elahi et al., 2016 ; Merimi et al., 2021 ; Sargent et al., 2018 ), proteomics ( Billing et al., 2016 ; Kehl et al., 2019 ), and secretome analysis ( Mizukami et al., 2019 ; Petrenko et al., 2020 ; Shin et al., 2021 ; Wangler et al., 2021 ). However, while data gleaned from these studies somewhat complement conclusions drawn from phenotypic analysis, one major drawback is that each of these studies focus on a different profiling methodology, which makes it difficult to establish a molecular equivalency among the various datasets.…”
Section: Introductionmentioning
confidence: 99%
“…Previous results indicated that under inflammatory circumstances, foreskin stem cells may act as specialized antigen-presenting cells [ 5 ]. Mechanistically, these functions are supported mainly by paracrine pathways [ 6 ]. Indeed, several factors play a key role in the adhesion, migration, and chemotaxis of MSCs, but the exact mechanism of homing is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A recent profiling highlighted that following a combination of inflammatory and proliferative signals, the sensitivity and responsive capacity of AT-MSCs were significantly modified (Merimi et al, 2021a). In particular, inflammation leads to an upregulation of IL-6, IL-8, IL-1β, TNF-α and CCL5 cytokine expression.…”
Section: In Vitro Toll-like Receptors Triggeringmentioning
confidence: 99%